Farmer seed systems for pigeonpea in coastal Andhra Pradesh - Bramel-Cox, P.J.; Kiran, S.; Reddy, U.; Varaprasad, K.S.; Chandra, S. (2004)
Seed is one of the main inputs in all cropping systems. Farmers take utmost care in seed selection as poor quality seed material can result in poor harvests and even crop loss. Seed systems can be classified as farmer and formal seed systems. In the target areas in north coastal Andhra Pradesh, pigeonpea is grown as a subsistence crop and farmer seed systems predominate. Both farmer and formal seed systems operate in the Telangana region where crops are grown with a market orientation. The farmers crop and seed system in these target areas are described by Kiran et al (2002]. The general flow of seed exchanges for these farmers is diagramed in Figure 1.Farmers in this region refer to seed rather than variety when they obtain seed from outside their own saved seed. This may be the same variety but another source of the ‘seed’. A number.of factors can influence the shift to a new seed or variety and they can be classified into environmental, social/psychological or other causes. The most common environmental loss experienced by these farmers is crop loss due to drought. Social/psycho logical causes could influence the desire to have a new crop, variety or seed due to increased knowledge or the need to bring in more income. Economic incentives include the need to change crops or varieties for increased production or to meet new market opportunities or economic conditions in the area favoring different land use, or government policies that favor other crops or varieties. Once the decision to obtain new seed is taken, farmers in the north coastal regions go to sources either within or outside the village. When sourced from outside the village, it can be from relatives, other farmers, weekly ‘shanties’ or markets, or from governmental institutions such as ITDC. This seed is acquired in exchange for cash or as a loan or gift. Understanding the possible sources of seed exchange as well as the frequency of this exchange is necessary to understand the risk of genetic erosion or loss in pigeonpea.